PROYECTO DE FACTIBILIDAD PARA LA IMPLEMENTACIÓN DE UN ALBERGUE PARA MASCOTAS CANINAS EN LA CIUDAD DE LOJA - Zambrano Masache, Gabriela (2015)
This research's main objective: Perform Project feasibility of implementing a shelter pet marbles. And the complete analysis of the project requires the implementation of specific objectives: market research, technical study, administrative and legal study, economic, financial study and finally evaluation. To study the following research methodology was used: the deductive method yielded valid conclusions by determining whether it is viable or not the creation of the project and the analytical descriptive method this method was used during the development of the entire investigation. In a survey results are applied to both buyers and sellers of the City of Loja to determine the acceptance of service on the market. Within the discussion the market study was established where demand ; being able to obtain the unsatisfied demand, then the marketing plan, pricing, place and advertising service is set; The technical study the size and location of the plant is detailed; In the administrative and legal study of determine the company provides business group, the constitution, organization and functions manuals. In the financial investment necessary study notes to implement the project the same which is $14.346,40 Finally the assessment for which the following indicators were analyzed was made: Net Present Value of $. 35486,74 ; Internal Rate of Return of 53,28%; 5 Benefit Cost Ratio is 1,46 for every dollar the company earns $ 0.46 cents; Capital Recovery Period is 43 month and 9 days; Sensitivity analysis indicates that the project supports an increase in the cost of 23,70% and the sensitivity analysis on the decline in revenues 30%, therefore this project is feasible, the conclusions and recommendations so determined, accompanied by the bibliography consulted with their respective attachments.